2016
DOI: 10.3928/00904481-20160310-01
|View full text |Cite
|
Sign up to set email alerts
|

Slipped Capital Femoral Epiphysis in Atypical Patients

Abstract: When patients who are thin present with knee pain, it can be easy to overlook the possibility of slipped capital femoral epiphysis (SCFE). Although 80% of patients with a "slip" are obese, thin children are not immune to this problem. Endocrinopathies, especially hypothyroidism, can be associated with SCFE. This article describes guidelines for evaluating patients for a slip and highlights some important considerations for the atypical SCFE. Patients with open growth plates with thigh or knee pain should routi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Characteristically, SCFE occurs when the metaphysis migrates anterosuperiorly relative to the physis. 4 In severe cases, this is easily seen in an AP view of a hip. However, in mild cases where minimal displacement occurs, this is not obvious and frog-leg lateral views of the hip become important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristically, SCFE occurs when the metaphysis migrates anterosuperiorly relative to the physis. 4 In severe cases, this is easily seen in an AP view of a hip. However, in mild cases where minimal displacement occurs, this is not obvious and frog-leg lateral views of the hip become important.…”
Section: Discussionmentioning
confidence: 99%
“…Less common associated disorders include endocrinopathies such as hypothyroidism, hypogonadal states and renal osteodystrophy. 4 An impact of environmental and genetic factors on the development of SCFE has also been suggested. 3 …”
Section: Introductionmentioning
confidence: 99%
“…A review of current literature shows that the presence of endocrine disorders in children with SCFE is significantly higher than in the general pediatric population [ 3 ]. Various papers have emphasized the need to consider metabolic and endocrine disorders as primary diagnoses for SCFE, especially in patients of noticeable short stature and sexual immaturity [ 2 - 3 , 10 ]. We recommend that a pituitary tumor be considered as a possible underlying cause in children presenting with SCFE.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The other varieties of SCFE are atypical and are associated with various pediatric endocrine and metabolic disorders as well as chronic diseases. 7 Loader et al reviewed 85 cases in which endocrine disorders were associated with SCFE and found that 40% had hypothyroidism, 25% had growth hormone deficiency and the remaining 35% had other conditions such as panhypopituitarism and hyperparathyroidism. 8 In that report, 5.2 to 6.9% of patients with SCFE were associated with endocrine disorders.…”
Section: Introductionmentioning
confidence: 99%
“…9 In literature, other recognized causes of atypical SCFE include growth hormone therapy, renal osteodystrophy, vitamin D deficiency, irradiation therapy, Down syndrome and Klinefelter mosaic state. [7][8][9][10][11] The association between SCFE and overweight/ obesity is better recognized than its association with various endocrine disorders. Therefore, in clinical practice, the latter association is more likely to be overlooked, 5 resulting in missed/delayed diagnosis.…”
Section: Introductionmentioning
confidence: 99%